Efektivitas Game Edukasi “Mahameru Saga” dalam Meningkatkan Literasi Mitigasi Erupsi Gunung Semeru pada Siswa MTsN 6 Malang - Hamim Thohari Mahfudhillah; Nayla Ramadhani Amanullah; Nabila Aisyah Paramitha; Neni Naqiyah (STKIP Subang, 2026)
Mount Semeru is an active volcano in East Java that poses eruption risks to surrounding communities. This situation necessitates strengthening disaster mitigation literacy through interactive and contextual learning. This study aimed to evaluate the effectiveness of the educational game